Systemic and Mucosal B and T Cell Responses Upon Mucosal Vaccination of Teleost Fish - Muñoz-Atienza, Estefanía; Díaz-Rosales, Patricia; Tafalla, Carolina (Frontiers in Immunology, 2021)
The development of mucosal vaccines against pathogens is currently a highly explored area of research in both humans and animals. This is due to the fact that mucosal vaccines have the potential to best elicit protective responses at these mucosal surfaces, which represent the frontline of host defense, thus blocking the pathogen at its initial replication sites. However, in order to provide an efficient long-lasting protection, these mucosal vaccines have to be capable of eliciting an adequate systemic immune response in addition to local responses. In aquaculture, the need for mucosal vaccines has further practical implications, as these vaccines would avoid the individual manipulation of fish out of the water, being beneficial from both an economic and animal welfare point of view. However, how B and T cells are organized in teleost fish within these mucosal sites and how they respond to mucosally-delivered antigens varies greatly when compared to mammals. For this reason, it is important to establish which mucosally-delivered antigens have the capacity to induce strong and long-lasting B and T cell responses. Hence, in this review, we have summarized what is currently known regarding the adaptive immune mechanisms that are induced both locally and systemically in fish after mucosal immunization through different routes of administration including oral and nasal vaccination, anal intubation and immersion vaccination. Finally, based on the data presented, we discuss how mucosal vaccination strategies could be improved to reach significant protection levels in these species.